Effect of Bi2O3 on radiation shielding properties of glasses from coal fly ash. (2018) - Rachniyom, W.; Chaiphaksa, W.; Limkitjaroeanporn, P.; Tuschaoen, S.; Sangwaranatee, N.; Kaewkhao, J.
Abstract: In the present work, the glasses were prepared by using sub-bituminous fly ash (SFA) and B2 O3 as raw material, Na2 O as fluxing agent. The effects of various Bi2 O3 concentration were investigated of the xBi2 O3 : (60-x)B2 O3: 10Na2 O: 30SFA (where x = 10, 15, 20, 25, 30, 35 by wt.%) by the melt quenching technique. The radiation shielding properties were measure by various photon energies from 220-662 keV, and compared between theoretical and experimental properties of the mass attenuation coefficients (µm ), the effective atomic numbers (Zeff ) and the effective electron densities (Ne ). All results were similar trend and good agreement between theoretical and experimental values. They were increased with increasing of Bi2 O3 concentration, and decreased with higher gamma rays energy. The half value layer (HVL) of glass samples demonstrated that the glasses had good shielding properties. The best glass in this work is 35wt.% of Bi2 O3 concentration and better than barite concrete.